Cities: Places of new European prosperity. Compendium of case studies on the socio-ecological transition of urban commons - Thomas Sauer; Susanne Elsen; Stefan Kuhn; Stephanie Barnebeck; Cristina Garzillo; Yannick Kalff; Judith Schicklinski (WWWforEurope, 2015)
Taking into account the potentially different starting and framework conditions of regions in different parts of the European Union, we will present a new approach for sustainability transition analysis. We hypothesise: favourable overall institutional conditions, such as a high degree of formal and informal local decision-making autonomy, are supportive for innovative institutional arrangements, like self-organised and co-operative forms of management of urban common pool resources. This report aims to explore these conditions systematically in the context of socio-ecological transitions with a special focus on the overarching research question: What is the transformative role of institutional diversification and innovation in the governance of core urban common pool resources? The role of the resource systems energy, urban green spaces and drinking water will be empirically analysed in the context of self-organisation and socio-ecological transition. Finally, policy recommendations based on these findings will be mapped.
Keywords: Q56; R11; D70; 330; Socio-ecological transition; Sustainable cities; Sustainable urban transitioning; Beyond GDP; Biophysical constraints; Multi-level governance